Efektivitas Media Bungker Terhadap Pemahaman Konsep Tabung-Kerucut Pada Siswa Kelas VI - Dicky Amirul Hasan; Lovika Ardana Riswari; Eka Zuliana (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Geometry learning, especially on the volume of cylinders and cones in elementary schools is often faced with obstacles in students' conceptual understanding, mainly due to ineffective learning methods, such as lectures and the use of limited two-dimensional media. The purpose of this study was to improve students' conceptual understanding of grade VI on the material of cylinders and cones using the "BUNGKER" media. This study used a quantitative approach with a One Group Pretest-Posttest Design, the study involved 35 grade VI elementary school students in two schools in Kudus Regency, Central Java. Data were collected through pretests and posttests as well as observations, then analyzed using descriptive statistics and n-gain, but first tested for normality with the Shapiro-Wilk test. The results showed that the "BUNGKER" learning media proved effective in improving students' conceptual understanding of the material on the volume of cylinders and cones, indicated by a significant increase in the N-gain test per indicator, overall the "BUNGKER" media is recommended as an effective alternative learning strategy. Keywords: BUNGKER Media, Concept Understanding, Cylinder and Cone